Overcoming the clinical challenges of traditional ayahuasca: a first-in-human trial exploring novel routes of administration of N,N-Dimethyltryptamine and harmine - Dornbierer, Dario A.; Marten, Laurenz; Mueller, Jovin; Aicher, Helena D.; Mueller, Michael J.; Boxler, Martina; Kometer, Michael; Kosanic, Davor; von Rotz, Robin; Puchkov, Maxim; Kraemer, Thomas; Landolt, Hans-Peter; et al. (Frontiers in Pharmacology, 2023)
Recently, the Amazonian plant medicine “ayahuasca” – containing the psychedelic compound N,N-dimethyltryptamine (DMT) and numerous β-carboline alkaloids, such as harmine – has been suggested to exhibit beneficial effects in patients with affective and other mental health disorders. Although ayahuasca ingestion is considered safe, its pharmacokinetics/pharmacodynamics and tolerability profile pose some challenges and may limit the clinical applicability in vulnerable patient populations. While overdosing and the admixture of intolerable plant constituents may explain some of the common adverse reactions, the peroral route of administration may represent another relevant source of gastro-intestinal intolerabilities and unpredictable pharmacokinetics across users. To overcome these challenges, the present work aimed at creating ayahuasca-analogue formulations with improved pharmacokinetics and tolerability profiles. To this end, we developed peroral formulas and compared them with parenteral formulas specifically designed to circumvent the gastro-intestinal tract. In more detail, peroral administration of a capsule (containing purified DMT and harmine) was tested against a combined administration of an oromucosal harmine tablet and an intranasal DMT spray at two dose levels in an open-label within-subject study in 10 healthy male subjects. Pharmacokinetic and pharmacodynamic profiles were assessed by means of continuous blood sampling, vital sign monitoring, and psychometric assessments. Common side effects induced by traditional herbal ayahuasca such as nausea, vomiting, and diarrhea were significantly attenuated by our DMT/harmine formulations. While all preparations were well tolerated, the combined buccal/intranasal administration of harmine and DMT yielded substantially improved pharmacokinetic profiles, indicated by significantly reduced variations in systemic exposure. In conclusion, the combined buccal/intranasal administration of harmine and DMT is an innovative approach that may pave the way towards a safe, rapid-acting, and patient-oriented administration of DMT/harmine for the treatment of affective disorders.